2004
DOI: 10.1002/art.20691
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and geriatric correlates of functional status after total hip replacement

Abstract: Objective. To determine whether psychosocial factors, chronic diseases, and common geriatric problems are associated with poor physical function 3 years after primary total hip replacement (THR). Methods. We studied a sample of Medicare recipients in Ohio, Pennsylvania, and Colorado (n ‫؍‬ 922) who underwent primary THR in 1995 (mean ؎ SD age 73.1 ؎ 5.6 years, 32% men). Participants completed a questionnaire regarding lifestyle factors, medical history, and quality of life ϳ3 years after the surgery. Physical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
79
0
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 26 publications
7
79
0
4
Order By: Relevance
“…However, groups incorporating these factors found that education was an independent predictor of OA and surgical outcomes [2,4,10,13,18]. Biases may be introduced if considering the excluded determinants because there may be reverse causation between OA and occupation and/or income.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, groups incorporating these factors found that education was an independent predictor of OA and surgical outcomes [2,4,10,13,18]. Biases may be introduced if considering the excluded determinants because there may be reverse causation between OA and occupation and/or income.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, associations between education and surgical outcomes have been explored using numerous patient-reported outcome measures [2,8,16,24]. When investigating postoperative function, an American study found that lack of a college education was associated with poorer function after THA [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Primarily affecting the articular cartilage lining of freely moving joints, and commonly attributed to the aging process, this highly debilitating disease can be aggravated by a variety of medical comorbidities and biological factors other than age [6][7][8][9][10][11][12][13][14][15]. Depression, a frequently observed condition in the older population as well as among people with chronic and/or chronically painful health conditions is another aggravating factor [12,[16][17][18][19][20][21][22][23][24]. Given that osteoarthritis is largely irreversible and that older people are more likely than younger persons to have this condition, the goal of this editorial was to provide a brief overview of the role of depression in the pathway from osteoarthritis pathology to disability and to make appropriate recommendations for advancing clinical practice in this area [9].…”
Section: Introductionmentioning
confidence: 99%